Vitamin E attenuates homocysteine and cholesterol induced damage in rat aorta - KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2013)
Background: The aim of this study was to investigate the effect of vitamin E on homocysteine and cholesterol-induced damage of rat aorta. Methods: Wistar rats (all fed with a vitamin E poor diet) were divided into five groups. Control group was fed with the diet only, the second group received 1 mg kg(-1) day(-1) L-methionine in drinking water, the third group was fed with 2% cholesterol containing diet, the fourth group received L-methionine and cholesterol together, and the fifth group was fed with L-methionine and cholesterol and received intramuscular injections of vitamin E. After 4 weeks serum homocysteine, cholesterol and vitamin E levels were measured; aortas were removed; collagen and elastin and the major extracellular matrix components were evaluated microscopically as indicators of aortic degeneration. Aortic collagen content was measured by a colorimetric hydroxyproline assay. Results: Four-week diet supplementation with methionine and cholesterol caused a twofold increase in serum homocysteine and 22% increase in serum cholesterol levels; endothelial damage and degenerative alterations in the aortic media were observed, as indicated by the dissociation of elastic fibers and accumulation of collagen. Vitamin E completely prevented the accumulation of collagen and largely prevented aorta damage as shown by the morphological data. Conclusion: The results indicate that, even moderate increases in homocysteine and cholesterol levels are sufficient to induce vascular degeneration that may be prevented by vitamin E supplementation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Atherosclerosis; Aorta; Homocysteine; Cholesterol; Vitamin E; SMOOTH-MUSCLE-CELLS; PROTEIN-KINASE-C; ENDOTHELIAL DYSFUNCTION; VASCULAR-DISEASE; ALPHA-TOCOPHEROL; ATHEROTHROMBOTIC DISEASE; REDOX HOMEOSTASIS; GENE-EXPRESSION; METHIONINE LOAD; LYSYL OXIDASE